Asymmetric Hydrogenation of Aromatic Carbocyclic Rings and Thiophenes - Ye, Zhi-Shi; Shi, Lei; Zhou, Yong-Gui (Synlett, 2014)
Recent advance on asymmetric hydrogenation of aromatic carbocyclic rings and thiophenes has been described with the chiral ruthenium catalyst. It represents a great breakthrough in the area of asymmetric hydrogenation as well as opens up a new pathway for the facile synthesis of valuable optically active carbocyclic rings and dihydro- and tetrahydrothiophenes.
Keywords: asymmetric hydrogenation; naphthalenes; thiophenes; ruthenium; N-heterocyclic carbene